Aerial Ostia. Before and After E42 - Massimiliano David (mediaGEO soc. coop., 2019)
During the XXth century, numerous studies were carried out in the site of ancient Ostia, also thanks to the support of aerial photography. Starting from the "Topophotographich survey” realized by the Italian Army in 1911, up to the "Atlante di Ostia antica” realized in 1996, Ostia has become one of the most photographed from up high among archeological sites all around Italy. The analysis of aerial photographs allows to develop a research structured in two main branches: the study of the ancient city and of its urban development, and the transformation of the landscape conceived by archaeologists during the last century. Through aerial photographs it is possible to understand the impact of the extensive excavations carried out from 1938 onward under the will of the fascism on the occasion of the Universal Exhibition foreseen for 1942 in Rome (E42).